Sustainability and Local Identity: The Rocky Trail Program as a Strategy for the SDGs in Higher Education - Leonardo Chaves de Carvalho; Lia Raquel Toledo Brambilla Gasques; Joao Vitor Costa; Laura Roseli Pael Duarte; Vivina Dias Sol Queiroz; Luciana Contrera; Camila Celeste Brandao Ferreira Itavo; Albert Schiaveto de Souza (Journal of Sustainability Perspectives, 2025)
The Trilha Rupestre (Rocky Trail) Program, developed by the Federal University of Mato Grosso do Sul (UFMS), aims to strengthen culture and the local economy. It also fosters sustainable development in municipalities with archaeological sites and paleontological records. Focusing on the Cerrado-Pantanal ecological corridor, the program covers 90 rock art sites and 733 archaeological sites registered with the National Historical and Artistic Heritage Institute (IPHAN) in 16 municipalities. The initiative trains local communities and encourages sustainable practices, contributing to income generation while promoting environmental preservation. Structured around eight thematic axes (food, archaeology, architecture, art-ceramics, botany, geopaleontology, chemistry-pharmaceuticals, and tourism), the program promotes multidisciplinary development, integrating quality education and building more inclusive and sustainable communities. The partnership with the UNESCO Borders and Migration Chair brings a social innovation approach, combining cultural appreciation with the promotion of inclusion. Through educational and cultural actions, the program raises awareness among communities and tourists about the importance of archaeological sites, linking sustainability with the appreciation of historical heritage. The Trilha Rupestre Program is a notable example of how higher education can contribute to meeting the Sustainable Development Goals.